A Contested Freedom of Religion or Belief (FoRB) under the Majority Power: The Dynamics of Shia Community in Indonesia - Suheri, Suheri (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2024)
The concept of Islamic law in Indonesia is dynamic, dominating several sectors but often arising with controversial effects. One of the minority groups affected is the Shi'a Islam. From the government, the MUI (Indonesian Ulama Council) and "moderate" religious organizations campaign and manipulate anti-Shi'a discourse in Islamic law and blasphemy law as a basis of power to encourage dehumanization or marginalization of minority Islamic groups. Shi'a is often accused of blaspheming Islam as it is different from Sunni beliefs and disrupts public order. This study aims to describe the complexity of the problem and show the dynamics related to the existence of Shia, both leading to the worst violations of the FoRB concept (Freedom of Religion or Belief) or actions in interfaith relations. This article is a qualitative library study. This paper argues that the affirmative action movement between religions contributes positively to responding to the majority-minority conflict in Indonesia by strengthening the multidimensional function of human rights and spreading awareness at all grassroots levels, NGOs, and government officials. This study found that inter-community coexistence raises the awareness that no one has the privilege to deprive every human being of any right.